Nurse resilience, burnout, pandemic stress, and post-traumatic stress: A secondary analysis of a longitudinal cohort - Rachel G. Baskin; Linda C. Copel; Janell L. Mensinger; Heather Brom (PLoS ONE, 2025)
Background It is estimated that approximately one-fifth of nurses in the United States will leave the profession by 2027 due to stress and burnout caused by the COVID-19 pandemic. It is unknown how burnout, resilience, and post-traumatic stress changed during the first two years of the COVID-19 pandemic in frontline nurses. The primary aim of this study was to evaluate how resilience, burnout, and post-traumatic stress changed in hospital-based nurses from 2020 to 2022. Secondary objectives were to describe the relationships between them and test whether burnout and resilience mediated the relationship between pandemic stress and post-traumatic stress. Methods This was a secondary analysis of a longitudinal cohort study of hospital nurses who participated in the COVID-19 Study and Registry of Healthcare and Support Personnel (CHAMPS) Registry. Changes in resilience, burnout, and post-traumatic stress (PTS) were evaluated using repeated measures ANOVA. Path analysis was conducted using multiple regressions to identify whether burnout and resilience acted as mediators between pandemic stress and post-traumatic stress. Results Thirty-two participants were included in all four waves of the longitudinal study, with a range of 32 to 740 participants across all time points. Changes in PTS were significant, while changes in burnout and resilience were not. Eighty-nine participants were available for the regression models used to answer the secondary objectives. Burnout mediated the relationship between pandemic stress and post-traumatic stress, but resilience did not. In addition, adequate protective equipment was found to be a predictor of lower pandemic stress. Conclusions Post-traumatic stress peaked in 2020 during lockdown in the United States and decreased significantly by 2022. Resilience and burnout did not change between 2020 and 2022. The results of this study can guide healthcare organizations in providing frontline healthcare workers with mental health resources, especially at the outset of a pandemic.